Simulation Of Soliton Amplification In Micro Ring Resonator For Optical Communication - A. Afroozeh; I. S. Amiri; M. Bahadoran; J. Ali; P. P. Yupapin (My University, 2012)
A system consisting of a series of micro ring resonator (MRR) is proposed. Optical dark and bright soliton pulses propagating through the nonlinear waveguides are amplified. This system can be used in long distance communication system. The dark and bright soliton is input into the designed system. The nonlinear effect contributes to segregation of continuous soliton pulse into smaller pulses. In this way large bandwidth of optical signals can be obtained. The power amplification occurs when the soliton propagates along the MRRs systems. In this research the concern is the generation of amplified pulse of optical dark and bright soliton while propagating in the MRR device. Simulated results show the amplification of bright soliton in which the input power increases from 0.6 W to 10.9331 W and 7.684 W at the trapped wavelength of 1520.428 nm and 1519.912 nm respectively. Key words: Optical soliton; dark soliton; bright soliton; soliton amplification
Keywords: Dissipative soliton; Optical power; Optical Network Technologies